Transgenerational epigenetic effect of kings’ aging on offspring’s caste fate mediated by sperm DNA methylation in termites - Mamoru Takata; Michihiko Takahashi; Tomoki Ishibashi; Eisuke Tasaki; Olav Rueppell; Edward L. Vargo; Kenji Matsuura (Proceedings of the National Academy of Sciences, 2025)
The discovery of transgenerational epigenetic inheritance and the unraveling of its molecular mechanisms are currently solving previously puzzling challenges that Mendelian genetics based solely on DNA could not explain, leading to significant paradigm shifts across various fields of biology. There has been a long-standing controversy over the factors determining the caste fate of individuals in social insects. Increasing evidence supports heritable influences on division of labor. Here, we provide evidence that transgenerational epigenetic inheritance influences caste determination in a termite. We demonstrate that the age of the king influences the caste fate of offspring, with young kings’ progeny showing a higher tendency for reproductive differentiation compared to offspring from older kings (under controlled conditions). Then, we conducted a high-quality chromosome-level genome assembly for the Japanese subterranean termite Reticulitermes speratus . Genome-wide methylome analysis of kings’ sperm reveals a drastic change in DNA methylation patterns with aging. Among 39,399,411 CpG sites, 21,611 sites showed significant age differences in methylation levels. We identified 13 genes whose methylation levels are significantly different between young and old kings and suggestively correlated with the offspring’s differentiation into the reproductive pathway. Our results suggest that sperm DNA methylation, which changes with the age of kings, is a potential transgenerational epigenetic factor involved in offspring caste differentiation in a termite. These findings may have broad applicability to caste differentiation in social insects and to phenotypic plasticity more generally.